Drying characteristics of white radish slices under heat pump — Low-temperature regenerative wheel collaborative drying - Junhai Yan; Weinan Han; Ben Wei; Yin Liu; Long Gao; Longji Wang; Song Wang; Mingru Zhu; Ziheng Huo (Case Studies in Thermal Engineering)
To address the issues of low efficiency, high energy consumption, and poor quality associated with traditional food drying methods, this study proposes a heat pump–low-temperature regeneration wheel collaborative drying system. This system offers advantages such as a fast drying rate, high food drying quality, and low energy consumption. To further investigate its drying characteristics, drying experiments were conducted on white radish slices at temperatures of 35 °C, 40 °C, and 45 °C. The results indicate that, compared to heat pump drying, the collaborative drying mode exhibits significant advantages: drying time was greatly reduced, with a minimum reduction of 60 min at all temperatures. The maximum drying rate increased significantly, ranging from 17.04 % to 19.51 %. Energy consumption was noticeably reduced, decreasing by 7.48 %–11.68 %. Moreover, the effective moisture diffusivity improved by 7.98 %–11.49 %, product shrinkage decreased by 4.00 %–5.56 %, rehydration ratios increased by 3.25 %–8.20 %, and sensory evaluation improved by 17.29 %–38.09 %. Additionally, based on the experimental data, the Wang and Sing model was determined to be the most suitable mathematical model for describing the collaborative drying process, exhibiting a coefficient of determination (R2) exceeding 0.999. This research demonstrates that the heat pump–low-temperature regeneration wheel collaborative drying system has significant potential for market application due to its high product drying quality and low energy consumption.